Recrystallization of molybdenum wire doped with potassium-silicate - Yoo, M.K.; Hiraoka, Y.; Choi, J. (Springer-Verlag, 1995)
The doping effect of the bubble formation oxide on the recrystallization of Mo wire was investigated. Five different wires of 1 mm in diameter were prepared through sintering, swaging, and drawing processes. Each wire was doped with various amounts of potassium (K) plus silicon (Si), i.e., 0, 0.028, 0.14, 0.28, and 0.49 by weight percent, and annealed for 30 minutes at given temperatures. To understand the overall recrystallization phenomena, changes in hardness and in optical microstructures were examined. Transmission electron micrographs were taken for the specimens in the as-drawn state and at the beginning of the decrease in hardness. And also, the relative excess resistivity was measured as a function of heating temperature to confirm the occurrence of the abnormal grain growth. During the grain growth, bubble dispersion was evaluated through fractography by scanning electron microscopy (SEM). Primary re-crystallization started at 750 °C regardless of the amount of dopants. For the specimens doped with 0.14 and 0.28 (K + Si), large elongated and interwoven grain structures indicating ab-normal grain growth developed over 1400 °C and 1600 °C, respectively. For the specimens doped with 0.028 and 0.49 (K + Si), however, small equiaxial grain structure developed similar to pure molybdenum wire. Such a difference was understood through the relationship between grain structures and bubble dispersion parameters (the average bubble diameter, the bubble row density, the columnar bubble spacing, and the bubble row distance). It was concluded that two of the most important parameters to develop a grain structure of high aspect ratio were bubble row density and bubble row distance. At a high bubble row density, irregularity in bubble row distance induced the higher aspect ratio (length/width (L/W)) of grain. ？ 1995 The Minerals, Metals & Material Society.
Keywords: Aspect ratio; Bubble formation; Doping (additives); Grain growth; Hardness; Metallographic microstructure; Potassium; Recrystallization (metallurgy); Silicates; Sintering; Transmission electron microscopy; Wire; Bubble dispersion; Bubble row density; Bubble row distance; Dopants; Grain structure; Molybdenum